Hidradenocarcinoma involving the male breast: Report of a case with emphasis on the differential diagnosis of invasive carcinoma with sweat gland differentiation - Eun Young Kang; Sarah B. Fisher; Lavinia P. Middleton (Elsevier, 2023)
A 41-year-old male presented with a 2-month history of a palpable peri-areolar nodule in the right breast. The patient underwent an excisional biopsy, which revealed a solid and partially cystic mass in breast parenchyma with an infiltrative border characterized by a solid and papillary proliferation of cells with clear or eosinophilic cytoplasm demonstrating cytologic atypia, numerous mitotic figures (>20/10 high-power fields), and areas of necrosis. Immunohistochemical analysis showed the tumor cells were faintly positive for p63, negative for SMMS, and strongly and diffusely positive for estrogen, progesterone, and androgen receptors. The tumor cells were equivocal for HER2 overexpression by immunohistochemistry and negative for HER2 amplification by fluorescence in situ hybridization (FISH). Tumor cells were also negative for MAML2 rearrangements by FISH. Diagnosis was consistent with hidradenocarcinoma. Preoperative staging with a mammogram, breast and axillary US, and breast MRI did not reveal evidence of residual tumor or metastases. The patient subsequently underwent a wide local excision and sentinel lymph node biopsy, which were negative for residual tumor. We report the first case of a hidradenocarcinoma of the breast originating in the deep breast parenchyma of a male patient and highlight the challenges in diagnosing this rare tumor, which can mimic a primary breast carcinoma.